1999
DOI: 10.1159/000030404
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Penile Carcinoma: Our Experience from 1976 to 1997

Abstract: Objective: The purpose of this work is to evaluate our experience with the surgical treatment of penile squamous carcinoma, analyzing the therapeutic results in terms of local recurrence rates, survival and mortality rates. Material and Methods: From 1976 to 1997, 47 patients were treated at our institution for carcinoma of penis. Treatment of primary tumor was conservative in 8 patients (17%). Partial penectomy was performed in 30 patients (63.8%); total penectomy in 5 (10.7%) and emasculation in 4 (8.5%). Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Local recurrence, as high as 56%, more commonly occurs after organ-preserving procedures applied for T2 or T3 tumours [45,46].…”
Section: General Considerationsmentioning
confidence: 99%
“…Local recurrence, as high as 56%, more commonly occurs after organ-preserving procedures applied for T2 or T3 tumours [45,46].…”
Section: General Considerationsmentioning
confidence: 99%
“…Ficarra et al [8] reported an overall survival rate of 34% in 47 patients with penile cancer because systematic lymphadenectomy was not performed and because conservative treatment was not given in some stage T1 cases. In a previous study, we found that p53-negative patients had 5-and 10-year overall survival rates of 64.5% and 54.6%, versus 30.2% and 26.4% in p53-positive patients, respectively-a statistically significant difference by univariate analysis [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, p53 translated from a mutant gene has a longer halflife, in opposition to the wild-type protein. Because both share epitopes, the mutated protein can be detectable by immunohistochemistry (IHC) [7,8]. Lopes et al [9] correlated the overexpression of p53 protein with an unfavorable prognosis in PC.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that are associated with penile squamous cell carcinoma include cigarette smoking, physical inactivity, and other infections of the penis, whereas a protective role of neonatal circumcision has been suggested [37]. Total or partial penectomy is, traditionally, the standard therapy of penile carcinoma and local control rates of > 90% can be achieved [12,25]. However, its significant effects on quality of life have led to the development of several organ-preserving techniques [1,5,18,30].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid an unacceptable local recurrence rate, a 1.5-2 cm margin of resection is necessary and, traditionally, the standard treatment of penile cancer. Partial or total penectomy guarantees excellent local control rates [12]. However, radical surgical treatment strategies have been associated with significant impairment of sexual function and quality of life [25].…”
Section: Introductionmentioning
confidence: 99%